Self-Efficacy in Primary School Teachers - Rahmawati, Arni Nur; Wirakhmi, Ikit Netra (Indonesian Journal of Global Health Research, 2024)
One of the teaching workers is elementary school teachers. Teachers are a vulnerable group and are at risk of experiencing problems in physical and psychological health. The psychological health problem that is often encountered in teachers is work stress. Teachers who experience work stress can be identified through their absence from class, increased emotions, and the illnesses they experience. One way for teachers to reduce work stress is to build self-efficacy. Self-efficacy is a belief in the teacher's ability to carry out teaching tasks. This research aims to determine the description of self-efficacy in elementary school teachers. This type of research is quantitative descriptive with a cross sectional approach which was carried out in elementary schools in the working areas of the Kembaran Regional Headquarters Office and the Purbalingga National Education Department Korwilcam Office. The sampling technique uses purposive sampling technique. The sample size of elementary school teachers was 25 people. The research instrument is the Teacher Sense of Efficacy Scale (TSES) questionnaire consisting of 12 items. The analysis used is quantitative descriptive. The results of this research show that 25 teachers have moderate category self-efficacy, indicated by the highest score in class management abilities. Teacher self-efficacy is the teacher's ability to engage students, classroom management, and teaching. Teacher self-efficacy is very important to be able to optimize teacher performance in the learning process.